Waiting for a Fruitful Crossroads among Those who Today Circulate in Parallel along the Educational Paths of Equity, Social Justice, Inclusion, Coexistence, Culture of Peace or Global Citizenship - Gerardo Echeita (Universidad Autónoma de Madrid, 2019)
Undoubtedly, it is morally and socially unfair that, from an educational point of view, many students from families with low economic resources are almost obliged to go to school in schools where the majority of classmates live in economic and social circumstances similar to they. The result, as Murillo and Martínez-Garrido (2019) have studied, is a "school segregation" for economic reasons that has the effect of creating a perverse vicious, social and academic circle. Those schools unfortunately become "ghettos", since the majority of their students belong to a social class with low resources, -with which this has little attraction for other families (Save the Children, 2016) - and, they create a school factor that the available research has shown to be very negative for the learning and student performance.